Comparing the physical principles of action of suspension damping devices based on their influence on the mobility of wheeled vehicles - Dushchenko, Vladislav; Vorontsov, Serhii; Masliyev, Vyacheslav; Agapov, Oleg; Nanivskyi, Roman; Cherevko, Yurii; Masliiev, Anton (Eastern-European Journal of Enterprise Technologies, 2021)
This paper reports the comparison of two physical principles of action of suspension damping devices based on their influence on the mobility indicators for an 8×8 wheeled machine. A radical difference between these principles of action is the dependence of resistance forces on the speed of the relative movement of working bodies (internal friction: hydraulic shock absorbers) or on the relative movement of working bodies (external friction: friction shock absorbers). Widespread hydraulic shock absorbers have certain disadvantages that do not make it possible to further increase the mobility of wheeled or tracked vehicles without the use of control and recuperation systems. In turn, in friction shock absorbers, the use of new materials has eliminated many of their shortcomings and thus can provide significant advantages. It was established that the application of friction shock absorbers for a given wheeled vehicle did not significantly affect the speed compared to hydraulic ones. The main factor that prevented the implementation of the advantages of friction shock absorbers was the insufficient suspension travel. However, friction shock absorbers absorbed 1.76...2.3 times less power, which reduced the load on nodes and increased efficiency (autonomy). In addition, a more uniform load on suspensions was ensured, which improved their resource, and, due to the prevailing vertical oscillations of the suspended body over the longitudinal-angular ones, the geometric passability improved as well. The comparison of two physical principles of action of damper suspension devices in a wheeled vehicle has shown that the use of friction shock absorbers could provide significant advantages in resolving the task relates to improving the mobility and would fundamentally affect the choice of the suspension energy recuperation system if it is applied.